Analisis Kuantitatif Pengisian Rekam Medis Elektronik Rawat Jalan di Poli Kulit Rumah Sakit X - Fatmawati Bakri Noor; Galih Persadha; Maghfirah Maghfirah (UPPM Politeknik Unggulan Kalimantan, 2024)
Quantitative analysis was conducted by examining the completeness of electronic medical record (EMR) documentation, which consists of four aspects: patient identification review, critical reporting, authentication, and proper documentation. This study aims to assess the completeness and accuracy of outpatient EMRs in healthcare facilities at Hospital X. The research is a descriptive quantitative study. The sampling technique used was total sampling, resulting in 52 EMR samples. The findings indicate that patient identification review requires improvement, as the incompleteness rate is relatively high (51.92%). Critical reporting also needs enhancement to ensure accurate information for medical decision-making. The authentication of electronic medical records showed fairly good results, although some records still did not meet the standards. Meanwhile, the proper documentation aspect achieved 100% completeness, demonstrating full compliance with documentation standards. In conclusion, although there has been progress in some aspects of medical documentation, further improvements are needed in patient identification and critical reporting to enhance healthcare quality and patient safety.